Behavioral effects in knowledge and awareness attribute for the Green Campus Management (GCM) - Rusli, Nazrul; Mohd. Hussain, Mohd. Ramzi; Nizarudin, Norhanis Diyana; Sabri, Syikh Sazlin Shah; Abdul Hamed, Sapiah (Otago Polytechnic, 2025)
Green Campus Management (GCM) is a strategic approach for higher education institutions to achieve sustainability goals. A critical attribute of GCM’s success is its ability to foster pro-environmental behaviors among campus stakeholders through enhanced knowledge and awareness. This literature review synthesizes research from 2020 to 2025 to examine the behavioral effects of the knowledge and awareness attribute within GCM frameworks. As illustrated in research, key studies reveal that environmental attitudes, behavioral intentions, and personal norms often mediate this relationship. The review also highlights that positive stakeholder perceptions and institutional commitment to green paradigms are crucial for inserting a sustainable culture. Conversely, a lack of proper planning can undermine these behavioral effects. In conclusion, knowledge and awareness are not merely informational attributes but are dynamic drivers of behavioral change within GCM. The effectiveness is maximized when integrated with supportive institutional systems that motivate and enable the campus community to act upon their knowledge, thereby realizing the overarching objectives of campus sustainability. This research contributes to the growing discourse on sustainable development in higher education institutions by offering strategic insights for policymakers and campus administrators to foster a culture of sustainability through behavioral change.